Distribution of Japanese Encephalitis Virus, Japan and Southeast Asia, 2016–2018 - Kuwata, Ryusei; Torii, Shun; Shimoda, Hiroshi; Supriyono, Supriyono; Phichitraslip, Thanmaporn; Prasertsincharoen, Noppadol; Takemae, Hitoshi; Bautista, Reu Caesar James Taga; Ebora, Valeen Drex Bendette Mendio; Abella, Jose Alexander Cabiling; Dargantes, Alan Payot; Hadi, Upik Kesumawati; et al. (Emerging infectious diseases, 2020)
During 2016-2018, we conducted surveillance for Japanese encephalitis virus (JEV) in mosquitoes and pigs in Japan, Thailand, the Philippines, and Indonesia. Phylogenetic analyses demonstrated that our isolates (genotypes Ia, Ib, III, IV) were related to JEV isolates obtained from the same regions many years ago. Indigenous JEV strains persist in Asia.